2017
DOI: 10.1080/02670836.2016.1258155
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and properties of Nb-bearing high-strength low-alloy surfacing layers

Abstract: Based on Q345 steel, high-strength low-alloy surfacing layers with Nb content ranging from 0.0041 to 0.26 wt-% were prepared by adding Nb element into electrode coating and manual electric arc welding, the microstructure as well as mechanical properties of surfacing layers were evaluated and analysed. The experimental results show that with the increasing of Nb content, the grain size becomes smaller meanwhile the microstructure distribution is more uniform, the size of hard phase martensite/austenite graduall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Hardfacing is a surface treatment method to apply a hard, abrasion resistant material to the surface of a less abrasion resistant substrate such as steel by plating, welding, spraying or other deposition techniques [1,2]. Among these deposition techniques, the welding processes are preferable for depositing hardfacing alloys including manual metal arc welding, submerged arc welding, and self-shielded flux-cored arc welding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hardfacing is a surface treatment method to apply a hard, abrasion resistant material to the surface of a less abrasion resistant substrate such as steel by plating, welding, spraying or other deposition techniques [1,2]. Among these deposition techniques, the welding processes are preferable for depositing hardfacing alloys including manual metal arc welding, submerged arc welding, and self-shielded flux-cored arc welding.…”
Section: Introductionmentioning
confidence: 99%
“…Another way to improve the wear resistance, together with fracture toughness, over that of high-chromium iron-based hardfacing alloys is to add strong carbide-forming elements such as Nb and Ti to obtain MC-type carbides, which are harder and finer than M 7 C 3 carbides. Wang et al [1] found that the yield and tensile strength of Nb-bearing high-strength low-alloy surfacing layers greatly increased for the fine-grain strengthening of Nb and the precipitation strengthening of NbC, and the impact toughness was significantly improved due to the microstructure variation and obvious grain refinement. Maja et al [5] researched the addition of Nb which increased the fracture strength due to the finer eutectic microstructure in the hypoeutectic high-chromium white cast irons.…”
Section: Introductionmentioning
confidence: 99%